Transfer of Nitrogen and Phosphorus From Cattle Manure to Soil and Oats Under Simulative Cattle Manure Deposition - Zhao, Chengzhen; Hu, Juan; Li, Qiang; Fang, Yi; Liu, Di; Liu, Ziguang; Zhong, Rongzhen (Frontiers in Microbiology, 2022)
Simulated cattle manure deposition was used to estimate nutrient transfer to soil and oats and to investigate changes in microbial community composition and functional groups in oat rhizospheres. Nutrient absorption and return efficiency were calculated a series of standard calculation formula and total nutrient transfer efficiency was nutrient absorption efficiency plus nutrient return efficiency. In total, 74.83% of nitrogen (N) and 59.30% of phosphorus (P) in cattle manure transferred to soil and oats, with 11.79% of N and 7.89% of P in cattle manure absorbed by oats, and the remainder sequestered in the soil during 80 days after sowing. Cattle manure increased oat root length, surface and volume under 0.2 mm diameter, and improved relative abundance of the microbiome known to be beneficial. In response to cattle manure, several bacteria known to be beneficial such as Proteobacteria, Bacteroidota and Firmicutes at phyla level and Pseudoxanthomonas, Pseudomonas and Sphingomonas at genus level, were positively related to oat biomass and nutrient accumulation. For fungal communities, the relative abundance of Ascomycota is predominant phylum, which varied in larger range in control treatment (81.0% to 63.3%) than cattle manure deposition treatment (37.0% to 42.9%) as plant growing days extend. The relevant abundance of Basidiomycota known as decomposer was higher in cattle manure deposition treatment compared to that in control treatment at 15 days after sowing. More importantly, cattle manure deposition inhibited trophic mode within pathotroph like Alternaria and Fusarium fungal genus and promoted saprotroph and symbiotroph.